Adaptive robust dual-loop control scheme of ship-mounted Stewart platforms for wave compensation. (October 2021) - Cai, Yunfei; Zheng, Shutao; Liu, Weitian; Qu, Zhiyong; Zhu, Jiyue; Han, Junwei
Highlights: Influence of ship motions on Stewart platform is fully considered. Velocity feedforward compensation is first proposed. It is the first dual-loop control method. Stability of system's equilibrium point is ensured. Abstract: Offshore installations e.g.marine transportation, oil platforms, etc., are strongly dependent on sea conditions. To increase the workable time of carrying out these operations, a Stewart platform is installed on a ship to serve as a motion compensation base, and equipment on the base can have the same precision with those on the land-fixed base. Herein, movements of the Stewart platform are influenced by ship motions. Consequently, they present more complicated dynamical characteristics. Besides, uncertainties coming from the load and the hydraulic system may deteriorate system performance. To deal with the aforementioned problems, this paper proposes an adaptive robust dual-loop control scheme. Specifically, a multiple-degree-of-freedom velocity feedforward compensator is proposed to decouple motion disturbance from the base platform. Furthermore, the original dynamics model is transformed into a linearly parameterized form, and adaptive laws are utilized to estimate essential parameters. Then, a command-filtered based adaptive robust controller is developed. Finally, it is rigorously proven that control errors are bounded employing Lyapunov-based analysis, and simulations are included to illustrate the effectiveness of the proposed control scheme.